Intravesical Chemohyperthermia vs. Bacillus Calmette-Guerin Instillation for Intermediate- and High-Risk Non-muscle Invasive Bladder Cancer: A Systematic Review and Meta-Analysis - Zhao, Hongda; Chan, Vinson Wai-Shun; Castellani, Daniele; Chan, Erica On-Ting; Ong, William Lay Keat; Peng, Qiang; Moschini, Marco; Krajewski, Wojciech; Pradere, Benjamin; Ng, Chi-Fai; Enikeev, Dmitry; Vasdev, Nikhil; et al. (Frontiers in surgery, 2021)
Background: The efficacy of intravesical chemotherapy maintenance for patients with non-muscle invasive bladder cancer (NMIBC) is inferior compared to intravesical bacillus Calmette-Guerin (BCG). How intravesical chemohyperthermia (CHT) compares with BCG is under investigation. Objective: To compare the oncological outcomes and safety profile between intravesical CHT and BCG treatment for intermediate- and high-risk NMIBC. Methods: We performed a systematic review and meta-analysis of clinical studies comparing CHT with BCG for intermediate- and high-risk NMIBC patients. A comprehensive literature search on OVID MEDLINE, EMBASE, and Cochrane Library was conducted. Risk of bias was assessed by the Cochrane RoB tool and ROBINS-I. Certainty of evidence was rated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: A total of 2,375 articles were identified and five studies were finally included. Among them, four randomised trials comprising 327 patients (CHT group: 156 patients; BCG group: 171 patients) were included in the meta-analysis. There were no significant differences in the 24-36 months recurrence rates (CHT: 29.5%, BCG: 37.4%; RR: 0.83, 95% CI 0.61-1.13; moderate certainty of evidence) and the 24-36 months progression rates (CHT: 4.4%, BCG: 7.6%, RR = 0.62, 95% CI 0.26-1.49; low certainty of evidence). There were also no significant differences in grade 1-2 adverse events (CHT group: 59.9%, BCG group 54.5%; RR = 1.10, 95% CI 0.93-1.30; moderate certainty of evidence) and grade 3 or above adverse events (CHT group: 23.2%, BCG group 22.5%; RR = 0.99, 95% CI 0.69-1.43; low certainty of evidence). Conclusions: Intravesical CHT had equivalent oncological outcomes and similar safety profile when compared to BCG maintenance therapy for patients with intermediate- and high-risk NMIBC. CHT is a possible alternative treatment in the times of BCG shortage.
Keywords: chemohyperthermia; BCG–Bacillus Calmette-Guérin vaccine; TURBT (trans-urethral resection of bladder tumour); bladder cancer; meta-analysis